Tectonic implication of the apatite fission-track analysis of the mylonites from the Terrane Boundary Shear Zone of the Eastern Ghats Mobile Belt around Lakhna, Orissa, India - BISWAL, TK; SEWARD, D (Gondwana Research, 2003)
Apatite fission-track analysis of the rocks within and adjoining the Terrane Boundary Shear Zone of the Eastern Ghats Mobile Belt, India, yield apparent ages ranging from 340+/-46 to 268+/-34 Ma. They are interpreted to be the result of slow (Ordovician to Recent) cooling/exhumation. Erosion rates are calculated at approximately 0.5-0.25degrees C/My. Genetic algorithm modeling suggests the possibility of a minor heating event at approximately 120 Ma; this is the time when the region was passing over Kerguelen hot spot as the Indian plate separated from Antarctica. The rocks within and outside the shear zone do not show any difference in age suggesting that there has been no movement (reactivation) along the shear zone during this drifting. Based on this assumption, the slightly higher rates of cooling, following this event, are attributed to continued slow denudation as well as thermal relaxation of the continent subsequent to hot spot influence.